Morphological Study of Right and Left Coronary Artery: A Cadaveric Study - Gautam, Ajeevan; Chaulagain, Rajib; Sintakala, Chandan; Yong, Kun Hing (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: The coronary arteries furnish the heart with its special arterial supply. The right coronary artery descends into the coronary sulcus after emerging from the right aortic sinus. The left coronary artery, which arises from the left aortic sinus, travels briefly via the coronary sulcus before splitting into two or three branches at the atrioventricular groove. This study aimed to estimate the standard size of the cadaveric heart and assess the morphological variation of the coronary artery. MATERIALS AND METHODS: An observational cross-sectional study was conducted at the dissection hall of the Anatomy department at Chitwan medical college. Twentyfour (24) human hearts present at the dissection hall and museum were used for the study. The weight of the heart was taken; a complete tracing of the coronary artery was done. Photographs were taken at different sites of dissection to find anomalies. Deformed specimens were excluded. RESULTS: Among 24 human hearts studied, the average weight was between 243gm to 322gm. The length of the heart was 11.02 to 11.89cm and the width was 7.97 to 8.56cm. The study reported right coronary dominance in 96% and left coronary dominance in 4% respectively. The study did not report any splitting of the right coronary artery but trifurcation of the left coronary artery was commonest (58%). CONCLUSIONS: This study concludes that the right coronary dominance is most common and the left coronary artery shows several variations than the right. The findings may be helpful in academic, medical, and surgical management like open heart surgery angioplasty.